Prosesi Pementasan Dan Persepsi Masyarakat Lampung Selatan Terhadap Barong Ket Dan Rangda Dalam Upacara Dewa Yajnya - Suyono, Suyono; Kristiyanti, Iluh (Metta : Jurnal Ilmu Multidisiplin, 2021)
Barong and Rangda dances are one of the art forms that exist in Balinese society. This dance is a traditional Balinese dance that uses a large animal mask with four legs. Barong and Rangda dance tells the story of the conflict between good and evil. The origins of Barong and Rangda are thought to have existed since the 16th century, during the reign of Dalem Waturunggung. This is indicated by the presence of Karang Bhoma, which is placed above the door or kori agung at the Paduraksa temple. In the form of barong and rangda, it seems that there is a mixture of Javanese artists with Balinese artists and has been influenced or inspired by Barongsae from China. In Sidowaluyo and Balinuraga villages, the Barong Ket and Rangda dances are performed at certain times, namely at large shrines at temples. However, not all people in the village know or understand the art of Barong Ket and Rangda and the reasons for their performance at the yajña ceremony. The purpose of this study was to determine the performance procession and the perceptions of the people of South Lampung towards the performance of Barong Ket and Rangda in dewa yajña ceremony.